Effect of catechins and high-temperature-processed green tea extract on scavenging reactive oxygen species and preventing Aβ1–42 fibrils' formation in brain microvascular endothelium. (3rd May 2020) - Lee, Seon-Bong; Choi, Eun-Hye; Jeong, Kang-Hyun; Kim, Kwang-Sik; Shim, Soon-Mi; Kim, Gun-Hee
Abstract : The present study investigated the effect of high-temperature-processed green tea extract (HTP_GTE) and its bioactive components on the reduction of reactive oxygen species (ROS) and amyloid-beta (Aβ) protein in human microvascular endothelial cells. Compared to Aβ1–42 -only treatment, pretreatment of HTP_GTE was revealed to effectively inhibit ROS generation ( P <0.05). HTP_GTE and catechins not only inhibit Aβ1–42 fibril formation but also destabilize preformed Aβ1–42 fibrils. The presence of HTP_GTE, Aβ1–42 fibril formation was significantly inhibited in a dose-dependent manner at 12.5–100 μg/ml of HTP_GTE, showing 86–56%, respectively. Treatment of various concentrations of HTP_GTE and catechins steadily destabilized the preformed Aβ1–42 fibrils for 24 h in a dose-dependent manner. It was observed that the gallated groups such as epigallocatechin gallate, epicatechin gallate, gallocatechin gallate, and catechin gallate more effectively disturbed Aβ1–42 fibril formation and destabilized the preformed Aβ1–42 fibrils than the non-gallated group. Taken together, these findings supported that sterilized green tea could be promising natural anti-amyloidogenic agents associated with therapeutic approaches in Alzheimer's disease by scavenging ROS generation and Aβ fibril in the brain tissue.